Relationship between tympanic membrane retraction and habitual sniffing in patients with cholesteatoma. (October 2013) - Takizawa, Yoshinori; Mizuta, Kunihiro; Hamada, Noboru; Yamatodani, Takashi; Nakanishi, Hiroshi; Hosokawa, Kumiko; Takahashi, Goro; Sugiyama, Kenichi; Mineta, Hiroyuki
Abstract Conclusion: Habitual sniffing affects the pathogenicity and recurrence of cholesteatoma. Postoperative instructions requesting patients to cease sniffing may reduce the retraction and recurrence of cholesteatoma. Objective: To examine the relationship between tympanic membrane retraction and habitual sniffing in patients with cholesteatoma. Methods: We recruited 98 patients (102 ears) who were surgically treated for cholesteatoma by canal wall-down tympanoplasty (22 ears) or canal wall-down tympanoplasty with reconstruction methods (80 ears). We classified these patients into two groups on the basis of their preoperative habitual sniffing: habitual and non-habitual sniffers. The findings of the contralateral tympanic membrane were examined in each group and were classified according to the Tos classifications. Next, we evaluated the incidence of 1-year postoperative tympanic membrane retraction treated by the canal-down tympanoplasty with reconstruction method in the following three groups: non-habitual sniffing group, sniffing cessation group, and continual sniffing group. Results: In habitual sniffers, the Tos classifications of contralateral tympanic membrane were normal in 7% (3/41). In contrast, for non-habitual sniffers, the findings were normal in 39% (21/54). These results indicate that sniffing causes tympanic membrane retraction. The tympanic membranes of patients in the sniffing cessation group were largely normal after surgery. However, more than 50% of the patients who continued to sniff after surgery showed retraction or recurrent cholesteatoma.